Developing written communication skills in engineers in Spanish: is ChatGPT a tool or a hindrance? - Mirón-Mérida, Vicente Antonio; García-García, Rebeca María (Frontiers in Education, 2024)
As 2023 became a disruptive year, due to the accelerated appearance of AI tools such as ChatGPT, the educational systems started to change and adapt to the new approaches observed in students, teachers, and employers. Although AI is likely to be integrated into different industrial and academic processes, its indiscriminate use could hinder the development of soft skills, including oral and written communication. Hence, it is important to identify any AI-generated assignments to secure a successful learning process. For those reasons, in this work, the effectivity of three plagiarism checkers, namely Turnitin, Unicheck and GPTZero, was evaluated on an engineering-based written text generated in ChatGPT in the Spanish language. A comparison with the plagiarism rate obtained for an original piece was conducted with One-way ANOVA. In all the cases, based on the low plagiarism rates (Unicheck: 14.44%, Turnitin: 12.43%), no plagiarism was detected in the AI-generated texts. Likewise, the GPTZero platform detected low AI-Origin in the texts created in ChatGPT (1.04%). Both results denoted the low efficiency of these platforms for assignments in Spanish and the high risk of conducting plagiarism without implications. Additionally, different alternatives were proposed for either integrating ChatGPT in learning activities or replacing the use of AI to ensure the development of skills and competencies in the students.